Attention to Diversity with Love and Respect. Inclusive, Equitable and Quality Education - Lalama Franco, Amor del Rosario; Morán Rodrigo , Miriam Maritza; Chenche Jácome, William Lenín; Zeballos Chang, Julia Lorena; Montenegro Ramírez, Rafael Fernando (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
Educational inclusion, equity and quality of education should be considered from the perspective of diversity, love and respect for students. The teacher is the architect of this variable education, which is why this research was conducted. The main objective is to understand the degree of relationship between the dimensions of inclusive, equitable and quality education. A quantitative correlational study was carried out under a non-experimental design, in which the perception of 384 teachers in the province of Guayas, all of them in initial and basic education, was collected through a survey. Cronbach's alpha was 92.5%.